SLAP Injury and the Superior Labrum - Jain, Abhishek; Aniq, Hifz; Mistry, Alpesh (Seminars in Musculoskeletal Radiology, 2022)
Injuries around the superior labrum are a common cause of shoulder dysfunction and pain. The injuries sustained result mainly from repetitive microtrauma but can also occur following a fall on outstretched hand. Both athletic and general populations can be affected. Injuries to the superior labrum are called superior labrum anterior and posterior (SLAP) tears. Based on cross-sectional imaging findings, the literature defines four main SLAP tears (I–IV) and six extended types (V–X). An accurate description of imaging findings of the SLAP tear type, along with concomitant findings, aids clinicians in treatment planning. We also briefly discuss management options, postoperative appearance of superior labral repair, and the diagnosis of a retear.
Keywords: glenoid labrum; superior labral tear; superior labrum anterior and posterior (SLAP)